2015
DOI: 10.1080/13102818.2015.1063452
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of dual-coated and uncoated mixture of probiotics in rats

Abstract: Probiotics have been used for the treatment of various disorders or as alternative therapies. The stability of dual-coated probiotics is increased in the gastrointestinal environment. The aim of the present study was to evaluate the hepatoprotective effects of dual-coated and uncoated probiotic supplements, following liver injury. Albino Wistar rats were orally treated with probiotics daily and carbon tetrachloride (CCl 4 ) was administered on the seventh and eighth days to induce acute liver damage. Hepatopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…(Table 1). The dose of VELGUT and VIZY-LAC was determined based on the preliminary experiments carried out before these experiments [10,18,19].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 1). The dose of VELGUT and VIZY-LAC was determined based on the preliminary experiments carried out before these experiments [10,18,19].…”
Section: Experimental Designmentioning
confidence: 99%
“…This shows that the probiotic treatment improved the histopathological status in all the animals. Therefore, it can be concluded that the probiotic treatment could have an antioxidant and anti-necrotic effect [32].…”
Section: T2mentioning
confidence: 99%